A flow cell culture apparatus - Arzmi, Mohd Hafiz; Mohd Nasir, Mohd Hamzah; Idris, Abdul Halim (2018)
Bacterial adhesion is an initial and critical step in the oral colonization process. Adhesion processes may include attachment of the bacterial cell to host cells, to components of the extracellular matrix (ECM), to the salivary pellicle on teeth and to soluble factors, as well as to bacterial cells of the same strain (auto-aggregation) or genetically distinct species (co-aggregation).